Understanding and Mastering Auditing Systems: A Key to Enhancing Educational Management and Organizational Accountability - Melyna Wijaya Putri; Reyhana Nur Azizah; Sofia Nisa Ulyantika; Heni Noviarita; Romlah (Al-Qalam Institue, 2026)
This study aims to analyze the concept of auditing systems and their role in enhancing organizational performance, focusing on the definition, objectives, functions, mechanisms, and outcomes. Using a qualitative approach, a literature review was conducted by examining relevant academic sources, including journals, books, and previous research. The findings show that auditing systems function as both control tools and strategic instruments for improving organizational effectiveness, efficiency, and accountability. They have evolved to include information system audits, emphasizing data security, system reliability, and operational effectiveness. Additionally, auditing systems contribute to strengthening internal control and risk management by identifying weaknesses and providing recommendations for continuous improvement. The study highlights the importance of auditing systems in enhancing transparency, accountability, and governance in modern organizations, including educational institutions. Effective auditing is essential for ensuring sound management practices and fostering an environment of trust and compliance.